Contribution of Host Nucleoporin 62 in HIV-1 Integrase Chromatin Association and Viral DNA Integration - Ao, Zhujun (American Society for Biochemistry and Molecular Biology, 2012)
HIV-1 integration is promoted by viral integrase (IN) and its cellular cofactors. The lens epithelium-derived growth factor (LEDGF/p75), an IN interacting cellular cofactor, has been shown to play an important role in HIV-1 chromatin targeting and integration. However, whether other cellular cofactors are also involved in viral replication steps is still elusive. Here, we show that nucleoporin 62 (Nup62) is a chromatin-bound protein and can specifically interact with HIV-1 IN in both soluble nuclear extract and chromatin-bound fractions. The knockdown of Nup62 by shRNA reduced the association of IN with host chromatin and significantly impaired viral integration and replication in HIV-1-susceptible cells. Furthermore, the expression of the IN-binding region of Nup62 in CD4(+) T cells significantly inhibited HIV-1 infection. Taken together, these results indicate that the cellular Nup62 is specifically recruited by HIV-1 IN and contribute to an efficient viral DNA integration.